A double modal synthesis approach for brake squeal prediction. (March 2016) - Monteil, M.; Besset, S.; Sinou, J.-J.
Abstract: This paper is devoted to propose a new efficient reduction method for predicting the stability analysis of a brake system subjected to friction-induced vibration. The finite element brake system under study is composed of a disc and a pad. The contact is modeled by introducing contact elements at the friction interface with the classical Coulomb law and a constant friction coefficient. It will be demonstrated that it is possible to build efficient reduced finite element models by developing a reduced model based on a Double Modal Synthesis (i.e. a classical modal reduction via Craig & Bampton plus a condensation at the frictional interface). Special attention is being conducted to validate the convergence of the reduced model especially on the approximation of the unstable modes with respect to real and imaginary parts. This complete numerical strategy based on Double Modal Synthesis allows us to perform relevance squeal prediction of unstable vibration modes. It is demonstrated that the numerical results via the Double Modal Synthesis are in good agreement with those of the classical Craig & Bampton method. Abstract : Highlights: Break squeal noise are studied via finite element method. The two systems are linked with a contact law applied to 220 contact nodes. A double modal synthesis is applied with a Craig and Bampton reduction and a Branch mode method. A convergence study is performed on the unstables modes responsible for the squeal noise.